2021
DOI: 10.1007/s11033-021-06919-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-induced transmembrane protein 2 promotes epithelial-mesenchymal transition by activating transforming growth factor-β1/small mother against decapentaplegic 2 signaling in gastric cancer

Abstract: Background Gastric cancer (GC) is one of the most prevalent malignancy around the world. Primary tumor cells are enabled to invade and migrate into adjacent normal tissues to form secondary tumors. Epithelial-mesenchymal transitions (EMT) plays a pivotal role in facilitating tumor progression. Abundant evidence suggested that the transforming growth factor-β1 (TGF-β1) triggered the process of EMT. Nonetheless, the precise molecular mechanisms underlying EMT requires further elucidation, and there still lacks e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…KEGG analysis revealed that IFITM2 was over-expressed in the Antigen processing and presentation, Cytokine and cytokine receptor interaction, Chemokine signaling pathway, Cell adhesion molecules, JAK-STAT signaling pathway and TGF-beta signaling pathway. In our previous study found that IFITM2 was the main component of TGF-β1 pathway that modulates EMT progression in GC (Liu et al, 2022). It has been previously reported that IFITM2 upregulation is associated with cytokine and cytokine receptor interaction functional pathways, and that IFITM2 is positively associated with VEGF-C expression and lymph node metastasis in renal cancer (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…KEGG analysis revealed that IFITM2 was over-expressed in the Antigen processing and presentation, Cytokine and cytokine receptor interaction, Chemokine signaling pathway, Cell adhesion molecules, JAK-STAT signaling pathway and TGF-beta signaling pathway. In our previous study found that IFITM2 was the main component of TGF-β1 pathway that modulates EMT progression in GC (Liu et al, 2022). It has been previously reported that IFITM2 upregulation is associated with cytokine and cytokine receptor interaction functional pathways, and that IFITM2 is positively associated with VEGF-C expression and lymph node metastasis in renal cancer (Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Recently, overexpression of IFITM2 has been found in colon carcinoma, renal clear cell carcinoma and osteosarcoma (Salas et al, 2009). Our previous study has demonstrated that the effect of IFITM2 on epithelial-mesenchymal transition in GC by activating TGF-β1 pathway (Liu et al, 2022). However, IFITM2 expression and its speci c mechanisms in GC remain unclari ed.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al found that IFITM2 has a high expression status in renal clear cell carcinoma tissues and cells, and can lead to tumor invasion and metastasis by promoting lymphangiogenesis [24] . Our previous study has demonstrated that the effect of IFITM2 on epithelial-mesenchymal transition in gastric cancer by activating TGF-β1 pathway [25] . However, IFITM2 expression and its speci c mechanisms in CRC remain unclari ed.…”
Section: Discussionmentioning
confidence: 98%
“…IFITM2 is a potential biomarker in some cancers, but its functional mechanism is still elusive [24][25][26] . In this study, we demonstrated that interfering with IFITM2 expression inhibited the proliferative potential of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation